The cultural tourism potential of a fashion-related exhibition – the case of Alexander McQueen: Savage Beauty at the Victoria and Albert Museum. Issue 2 (15th March 2017) - Calinao, Dan Jason; Lin, Hui-Wen
ABSTRACT: The exhibition Alexander McQueen: Savage Beauty held at the Victoria & Albert Museum (V&A) in London attracted a total number of 493, 043 visitors from both the UK and overseas, making it one of the most visited exhibitions throughout the museum's history. Much of the exhibition's popularity was drawn from the late designer's fame, reputation, and exceptional technique in design and clothing construction. The V&A museum also having the title as the greatest Museum of decorative arts and design, and founded during the late Victorian era, possesses heritage value that may also have played a role in attracting visitors to the Savage Beauty exhibition. Findings suggest that Savage Beauty appeals more on the local cultural tourism context for its connection to London. The V&A's heritage value as Grade I listed may be of minimal interest to tourists; however, visitor interest in London and the number of great museums in the city serves well enough to attract and enrich cultural awareness of potential tourists both local and international. Special exhibitions such as Savage Beauty may also prove effective in attracting tourists, leading to increasing cultural tourism once tourists learn more about London's culture, which includes fashion, but only in a derivative sense.